Kinesiological characterization of choku-tsuki done with impact and its comparison with its execution without impact (Revista de Artes Marciales Asiáticas, 2012)
Aim: This work aims to characterize the kinematics and electromyography of a basic karate punch (choku-zuki) made with an impact on a target (makiwara) by experienced karateka, and compares it with the execution without real impact on the target (control). This characterization allows to the coach (sensei) to know how training influences the performance of the punch in each one of these circumstances, and from that information it is possible to define strategies of training that considers adapted to its goals.Method: In a sample of ten male karateka of the Portuguese Karaté Team the kinematic and electromyographic data of the arm and forearm segments were collected during the execution of choku-zuki, with impact and no impact.Results: It was found that the kinematics and neuromuscular activity in the performance of choku-zuki happens in a time interval less than 300ms. The studied muscles activity and segments of the upper limb shows a trend of activation sequence with a proximal to distal direction, with the intervening segment arm muscles having a greater intensity of activation that the muscles involved in the forearm segment. The arm flexion at the shoulder joint and the forearm extension at the elbow joint are done with greater amplitude, and the forearm pronation is not complete at the time of impact. The forearm pronation at the elbow joint is not complete and tends to be the first segmental movement in the choku-zuki execution.Conclusion: The executions of choku-zuki with impact and no impact are kinesiologically different. This difference highlights the importance that coaches should provide to teach and training the punch execution with an effective impact on the target.